Sodium-Selenium Batteries with Outstanding Rate Capability by Introducing Cubic Mn2O3 Electrocatalyst - Erdol, Zeynep; Ata, Ali; Demir-Cakan, Rezan (Wiley-V C H Verlag Gmbh, 2024)
With their high volumetric capacity and electronic conductivity, sodium-selenium (Na-Se) batteries have attracted attention for advanced battery systems. However, the irreversible deposition of sodium selenide (Na2Se) results in rapid capacity degradation and poor Coulombic efficiency. To address these issues, cubic alpha-Mn2O3 is introduced herein as an electrocatalyst to effectively catalyze Na2Se conversion and improve the utilization of active materials. The results show that the addition of 10 wt% Mn2O3 in the selenium/Ketjen black (Se/KB) composite enhances the conversion from Na2Se to Se by lowering activation energy barrier and leads to fast sodium-ion kinetics and low internal resistance. Consequently, the Mn2O3-based composite delivers a high specific capacity of 635 mAh & sdot; g(-1) at 675 mA & sdot; g(-1) after 250 cycles as well as excellent cycling stability for 800 cycles with a high specific capacity of 317 mAh & sdot; g(-1) even at the high current density of 3375 mA & sdot; g(-1). Due to the cubic Mn2O3 electrocatalyst, the performance of the composites is superior to existing state-of-the-art Na-Se batteries reported in the literature.
Keywords: sodium-selenium batteries; metal oxide; cubic-Mn2O3; electrocatalyst; Na2Se deposition